(NwULKANIZM SREDNEJ ^ASTI wOSTO^NOGO sIHOT\(B-(NaLINQ (B:s ((Nu^ASTOK MYS dATTA (B- (NMYS s@RKUM(B) /s - (NeSIN(B, (NsERGEJ wALENTINOWI^s; (NkUTOLIN(B, (NwLADISLAW aLEKSEEWI^s; (NpRUSEWI^(B, (NaLEKSANDR aLEKSANDROWI^s ((NnOWOSIBIRSK (B:s (NiN(B-(NTA GEOLOGII I GEOFIZIKI so an sssr(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 51-55 (44 (NNAZW(B.)s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (NiN(B-(NT GEOLOGII I GEOFIZIKIs
Keywords: (NwULKANIZMs; (NsIHOT\(B-(NaLINX(B, (NGORYs